2015
DOI: 10.15446/profile.v17n2.44393
|View full text |Cite
|
Sign up to set email alerts
|

Reflective Teacher Supervision Through Videos of Classroom Teaching

Abstract: <p>The main objective of this paper is to briefly present roles of different teacher supervisors according to distinct models, highlighting the importance of collaborative dialogues supported by video recordings. This paper will present results from a qualitative study of an English as a foreign language teacher education course in Brazil. The results indicated that collaborative supervision was an efficient tool to address adversities within educational contexts and that student teachers who observed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 9 publications
0
6
0
2
Order By: Relevance
“…This model is based on effective interaction between the teacher and the supervisor in order provide teachers with feedback that is helpful in improving teachers' professional development and growth (Baltaci-Goktalay et al, 2014;Kaneko-Marques, 2015). Robinson (2000) showed that a clinical supervision style had a positive effect on the school overall performance as well as teachers' job satisfaction.…”
Section: Objectives Of the Studymentioning
confidence: 99%
“…This model is based on effective interaction between the teacher and the supervisor in order provide teachers with feedback that is helpful in improving teachers' professional development and growth (Baltaci-Goktalay et al, 2014;Kaneko-Marques, 2015). Robinson (2000) showed that a clinical supervision style had a positive effect on the school overall performance as well as teachers' job satisfaction.…”
Section: Objectives Of the Studymentioning
confidence: 99%
“…Por el contrario, la retroalimentación es entregada adoptando un enfoque directivo, con predominio de intervenciones informativas y y consejos (Glickman et al, 2014), en el marco de este estudio, por encontrarse las profesoras en formación en su última práctica y, por ende, a pocas semanas de integrarse al mundo laboral, una práctica de supervisión más colegiada, colaborativa y reflexiva hubiera sido deseable. Una supervisión colaborativa promueve la participación de los profesores en formación en su propio desarrollo profesional convirtiéndolos en sujetos activos en la toma de decisiones con respecto a la complejidad de la enseñanza y el aprendizaje (Kaneko-Marques, 2015). Para cumplir con estos objetivos los practicantes deben ser estimulados para reconstruir sus conocimientos y reflexionar sobre sus experiencias en el aula durante la práctica docente.…”
Section: Discussionunclassified
“…Debido a la existencia de distintos enfoques de supervisión, es relevante distinguir entre dos líneas. La primera, aquella centrada en el desarrollo de las competencias docentes desde un modelo colaborativo (Kaneko-Marques, 2015); la segunda, focalizada en la evaluación, generalmente asociada con modelos prescriptivos (Ward et al, 2011). No obstante, en la acción tutorial real, los sujetos pueden transitar entre estos enfoques dependiendo de las dimensiones, sentidos y significados atribuidos que se generen, lo que incide en que la reflexión posobservación tome cursos no previstos o planificados.…”
unclassified
“…Then, provision of on-going maintenance of reflective values within the arranged activities can be maximized through the principals' participation in the embrace and supervision stages in a collaborative atmosphere. The inclusion of ICT as a strategy embracing the concept of multimodality may also aid the promotion of the initiated reflective teaching programs (Kaneko-Marques, 2015). However, it is still in the form of training and education sessions from the central system, not in the schools.…”
Section: The Milestone Of Research On Reflective Teaching In Efl Contextmentioning
confidence: 99%